Prevalence of Periodontitis among Rheumatoid Arthritis Patients Attending Tertiary Hospital in Nepal - Shrestha, Sweta; Pradhan, Shaili; Adhikari, Binod (Journal of Nepal Health Research Council, 2020)
Background: Rheumatoid arthritis and Periodontitis both are chronic destructive inflammatory disorders characterized by dysregulation of the host inflammatory response and increase in localized and systemically circulating pro-inflammatory cytokines. The objective of this study was to determine prevalence of periodontitis among Rheumatoid Arthritis patients in our setup.Methods: A crossectional study was done in 43 cases of diagnosed Rheumatoid Arthritis patients visiting to department of Orthopedics of Bir Hospital during the period of July 2016 to January 2017 were examined for presence of periodontitis and its severity. A descriptive questionnaire was also prepared concerning age, sex, personal history. Parameters to be measured were Plaque Index, Gingival Index, Pocket Depth and Clinical Attachment Level.Results: Prevalence of periodontitis among Rheumatoid Arthritis patients was found to be 86.04% (37) with Mild periodontitis in 9%(4), Moderate periodontitis 56% (24)and severe periodontitis in 21% (9). The commonest age group was 50.41±9. with male to female ratio of 1:3Conclusions: Periodontitis was common in Rheumatoid Arthritis in our set up. Moderate periodontitis was more frequent. Periodic oral examination of patients with Rheumatoid Arthritis is required to improve periodontal health.Keywords: Host response; inflammation; periodontal pocket depth; periodontitis; pgingivalis rheumatoid arthritis.